Modality Auxiliary Verbs in English-Malay Translation: (Kata Bantu Ragam dalam Terjemahan Inggeris-Melayu) (Jurnal Bahasa, 2017)
This paper aims to investigate the translation of modal auxiliary verbs from English into Malay by a group of trainee translators in the Bachelor of Arts (Translation and Interpretation) programme at Universiti Sains Malaysia (USM). More specifically, the paper aims to determine areas which may pose difficulties for these students when translating modal auxiliary verbs from English into Malay. For this purpose, the students were given a test that required them to translate 11 items from English into Malay, focusing on the use of these. An analysis was then carried out on the translations provided by the students, which involved examination of the translated equivalents for each item, in terms of the meaning conveyed. The results of this study highlight the areas that students find problematic in translating modal auxiliary verbs, and points to possible areas which could be given greater attention in the teaching and learning of translation, particularly those involving such items.Keywords: modal auxiliary verbs, meaning, equivalents, translator training